(untitled) (Journal of Tikapur Multiple Campus, 2022)
This study examines the impacts of consumer rights awareness on buying behaviour in Kailali district of Nepal. The empirical study has collected data from primary sources based on a convenience sample of 418 consumers in different locations in Kailali district with a structured questionnaire to measure consumer awareness regarding the four basic consumer rights and their buying behaviour, utilizing a five-point Likert scale for measurement. The overall findings show that there is a significant positive association between consumers’ awareness rights and their buying behaviour. Moreover, the study indicated that the four dimensions of consumer rights imposed a positive impact on consumer buying behaviour. The study investigated the status of consumer rights awareness as the most important factor of changing consumer behaviour. The outcomes of the study can be important to understand the consumer rights and effect on their purchase behaviour and provide the reference to consumers, consumer forums, business firms, government units, policymakers, and researchers.